Renewable energy in infographics - Lowe, Alexander (Enviro-graphics., 2021)
Presents information about renewable energy through a collection of diagrams and charts. Discusses what renewable energy is, different types of renewable energy, how it works, and where it's used. Includes an activity, a glossary, and resources for further information.